Microplastics exposure: implications for human fertility, pregnancy and child health - Zurub, Rewa E.; Cariaco, Yusmaris; Wade, Michael G.; Bainbridge, Shannon A. (Frontiers in Endocrinology, 2024)
Plastics found in our everyday environment are becoming an increasing concern for individual and population-level health, and the extent of exposure and potential toxic effects of these contaminants on numerous human organ systems are becoming clear. Microplastics (MPs), tiny plastic particles, appear to have many of the same biological effects as their plastic precursors and have the compounded effect of potential accumulation in different organs. Recently, microplastic accumulation was observed in the human placenta, raising important questions related to the biological effects of these contaminants on the health of pregnancies and offspring. These concerns are particularly heightened considering the developmental origins of health and disease (DOHaD) framework, which postulates that in utero exposure can programme the lifelong health of the offspring. The current review examines the state of knowledge on this topic and highlights important avenues for future investigation.